Genealogi dan Persebaran Tarekat Qādiriyyah wa Naqsyabandiyyah Berjan Purworejo - Rizki Hidayatulloh (Hikamia: Jurnal Pemikiran Tasawuf dan Peradaban Islam, 2026)
This paper examines the genealogy and spread of Ṭarīqah Qādiriyyah wa Naqsyabandiyyah Berjan Purworejo. Shaikh Ahmad Khatib al-Sambasī, the founder of this tariqah, had a famous caliph, 'Abd Al-Karīm Al-Bantanī. From this caliph, a Purworejo named Zarkasyī ibn Asnawi received ijāzah murshid Ṭarīqah Qādiriyyah wa Naqsyabandiyyah which means that he has the authority to spread Ṭarīqah Qādiriyyah wa Naqsyabandiyyah and appoint the murshid of the tariqah. From this Shaikh Zarkasyī, Ṭarīqah Qādiriyyah wa Naqsyabandiyyah spread to various corners. With a library research method, whose data sources come from books or journals related to the research topic. The main source comes from the biography book of KH. Nawawi, the fourth murshid of Ṭarīqah Qādiriyyah wa Naqsyabandiyyah Berjan Purworejo, and several journals, it can be seen that the spread of Ṭarīqah Qādiriyyah wa Naqsyabandiyyah Berjan Purworejo includes Java, Sumatra, Kalimantan (especially Brunei Darussalam and Malaysia), and the Malay Peninsula.